Anisotropic and strain rate-dependent mechanical properties and constitutive modeling of the cancellous bone from piglet cervical vertebrae. (May 2020) - Li, Zhigang; Wang, Jinjin; Song, Guanghui; Ji, Cheng; Han, Xinfeng
Highlights: Compression tests were conducted on cervical cancellous bone of piglets (child surrogates) with strain rate ranging from 0.01/s to 10/s. Effects of direction and strain rate on the vertebral mechanical properties were statistically investigated. A strain-rate dependent transverse isotropic elastic-plastic constitutive model was developed to describe vertebral behavior. The developed model was implemented into LS-DYNA through user material subroutine (UMAT). The developed model and corresponding codes can well simulate the mechanical behavior of cervical cancellous bone. Abstract: Background and objective: Characterizing the mechanical properties of the cancellous bone from the cervical vertebrae of child or child surrogate is important for the development of spine finite element models and the investigation of injury mechanism, however, there is currently no public data available as far as we know. Methods: C ompression tests were conducted on the specimens from the cervical vertebrae of 8-week-old piglets (child surrogates) in axial and radial directions at the strain rates of 0.01, 0.1, 1 and 10/s. The influences of directionality and strain rate on the mechanical properties of the vertebral cancellous bone were statistically investigated. The typical transversely isotropic model, which was added a strain rate item and a plasticity item, was implemented into LS-DYNA finite element code. Based on the material subroutine code, simulation was conducted on the vertebral tissue under compression in axial and radial directions at different strain rates. Results: The mechanical properties of the cancellous bone of cervical vertebrae were obtained and most of the stress-strain curves showed major linear elastic stage and short plastic stage before fracture. Significant anisotropic behavior was observed for the vertebral tissue in axial and radial directions. The elastic modulus, ultimate stress, yield stress, and ultimate strain of the speimens in axial direction was obtained, with on average, 2.5 ± 0.6 times, 2.1 ± 0.15 times, and 2.1 ± 0.1 times higher and 0.86 ± 0.076 times lower respecitvely, than those in radial direction. In addition, with the strain rate varying from 0.01/s to 10/s, the mechanical parameters, like elastic modulus, yield and ultimte stresses exhibited significant strain rate effect, however, no significant difference was found for the ultimate strain. Conclusions: The cervical vertebrae showed significant anisotropic and strain rate-dependent behaviors. The self-developed subroutine codes based on the strain rate-dependent transversely isotropic elastic and plastic constitutive model can simulate the behaviors well.